Rhetoric, Political Ideology and the Peace Process in Colombia: A Twitter® Analysis (2019)
An ethos of violence based on political ideologies aiming to delegitimize an adversary is a psychosocial barrier to solving lasting conflicts, such as in Colombia. Beyond the signing of a peace agreement, the cessation of political violence implies modifying the complex symbolic dynamics constructed by various opposing actors to legitimize acts of direct violence. This research evaluates whether a new rhetoric that encourages the development of a peace culture has replaced the ideological rhetoric of various social actors involved in dialog and negotiations to end the armed conflict between the Colombian government and the Revolutionary Armed Forces of Colombia–People’s Army (FARC-EP). To this end, a textual analysis of the ideological rhetoric disseminated through Twitter® by several actors in Colombian society was conducted to identify the expressions used (semantic analysis) to legitimize or delegitimize those involved in the conflict in the last negotiation year (2016). The outcome indicates that the agenda of topics revolves around peace, and although the ideological differences between the negotiation table (i.e., the government and FARC-EP) and the opposition party are evident in the published messages, all the actors are striving to develop a rhetoric of tolerance and coexistence. © 2019, © 2019 Taylor and Francis Group, LLC.